Basic Concepts and Techniques of Feminist Counseling: A Literature Review - Ngampuni; Purwoko, Budi; Habsy, Bakhrudin All (Jurnal Indonesia Sosial Sains, 2026)
Feminist counseling has emerged as a significant psychological approach that addresses gender inequality, individual empowerment, and the critical awareness of oppressive social structures. This study aims to explore the basic concepts, historical development, theoretical foundations, and techniques of feminist counseling through a systematic literature review. Using a qualitative approach with literature study methods, this research synthesizes findings from various scholarly sources to provide a comprehensive understanding of feminist counseling as an applied framework in psychotherapy. The results reveal that feminist counseling originated in the late 1960s as a reaction to gender bias embedded in traditional psychotherapy, rooted in the second wave of the women's movement. Key figures such as Jean Baker Miller and Carol Gilligan contributed foundational perspectives that shaped the approach's core principles, including gender equality, egalitarian counselor-client relationships, and client empowerment. The counseling techniques identified include open dialogue, self-reflection, gender education and social awareness, client empowerment, deconstruction of gender roles, social advocacy, and narrative therapy. These techniques are designed to help clients—particularly women and female students—recognize their experiences within a broader sociocultural context, challenge internalized gender norms, and pursue greater personal autonomy. While feminist counseling offers distinctive strengths in promoting gender sensitivity and social justice, limitations include potential value imposition by counselors, reduced applicability for male clients, and ideological fragmentation among feminist schools of thought. This study concludes that feminist counseling plays a vital role in advancing gender equality and enhancing psychological well-being within contemporary society.